Lifetime Earnings Inequality in Germany - Holger Lüthen; Timm Bönke; Giacomo Corneo (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2012)
This paper documents the magnitude, pattern, and evolution of lifetime earnings inequality in Germany. Based on a large sample of earning biographies from social security records, we show that the intra-generational distribution of lifetime earnings of male workers has a Gini coefficient around .2 for cohorts born in the late 1930s and early 1940s; this amounts to about 2/3 of the value of the Gini coefficient of annual earnings. Within cohorts, mobility in the distribution of yearly earnings is substantial at the beginning of the lifecycle, decreases afterwards and virtually vanishes after age forty. Earnings data for thirty-one cohorts reveals striking evidence of a secular rise of intra-generational inequality in lifetime earnings: West-German men born in the early 1960s are likely to experience about 80 % more lifetime inequality than their fathers. In contrast, both short-term and long-term intra-generational mobility have been rather stable. Longer unemployment spells of workers at the bottom of the distribution of younger cohorts contribute to explain 30 to 40 % of the overall increase in lifetime earnings inequality.
Keywords: D31; D33; H24; 330